Ecopsychosocial strategies for the self-exploration of professional family caregivers to manage the behavioural and psychological symptoms of Alzheimer patients in Iran: a qualitative study - Kambiz Bahaadinbeigy; Parastoo Amiri; Zahra Niazkhani; Habibollah Pirnejad (BMJ Open)
Objective The aim of the present study was to explore the experiences and viewpoints of professional family caregivers in the management of behavioural and psychological symptoms of dementia (BPSDs) to identify the ecopsychosocial strategies applied by them.Design Qualitative study.Setting Kerman, Iran.Participants Stories were collected from 40 professional family caregivers of dementia patients.Measurement The guidelines of the National Consensus Project (NCP) of the USA served as the conceptual framework for the deductive thematic analysis of our qualitative data. A schematic of the entire process was performed in five steps.Results 30 stories relevant to the aim of this study were included in the analysis from April to June 2021. A majority of the stories were written by female caregivers. We identified 19 ecopsychosocial interventions, which covered the NCP dimensions except ‘Care of the patient nearing the end of life’. More than half of these interventions were classified into psychological/psychiatric and physical aspects of care (57.8%). In addition to the care/support provided by special care units or home care, some caregivers believe that support from the government, various care organisations, social media and even other family members/friends is necessary to better manage BPSDs.Conclusion Despite limitations, such as having a small sample size and analysing only one story from each caregiver, our results indicate that dementia caregivers need more educational and cultural support in their ecopsychosocial strategies. Government involvement would yield more positive outcomes in managing BPSDs.